Topical Protease Inhibitor Increases Tumor-Free and Overall Survival in CD4-Depleted Mouse Model of Anal Cancer - Evan Yao; Laura Gunder; Tyra Moyer; Kristina A. Matkowskyj; Kathryn Fox; Yun Zhou; Sakura Haggerty; Hillary Johnson; Nathan Sherer; Evie Carchman (Viruses)
Patients with immunodeficiencies and older age are at an increased risk of anal cancer. Transgenic K14E6/E7 mice with established high-grade anal dysplasia were treated topically at the anus with the protease inhibitor saquinavir (SQV) in the setting of CD4+ T-cell depletion to mimic immunodeficiency. To ensure tumor development, specific groups were treated with a topical carcinogen (7,12-Dimethylbenz[a]anthracene (DMBA)). The treatment groups included the vehicle (control), DMBA only, topical SQV, and topical SQV with DMBA, as well as the same four groups with CD4 depletion. The mice were monitored weekly for tumor development. Upon reaching 20 weeks of treatment, the mice were sacrificed, and their anal tissue was harvested for histological analysis. None of the mice in the SQV or control groups developed overt anal tumors, except three mice that were CD4-depleted. The CD4-depleted mice treated with DMBA had significantly increased tumor-free survival and overall survival as well as decreased tumor-volume growth over time when treated with SQV. These data suggest that topical SQV, in the setting of CD4 depletion and high-grade anal dysplasia, can increase tumor-free and overall survival; thus, it may represent a viable topical therapy to decrease the risk of progression of anal dysplasia to anal cancer.